The occurrence and molecular characterization of non-tuberculous mycobacteria in cattle, African buffalo (Syncerus caffer) and their environments in South Africa and genomic characterization and proteomic comparison with Mycobacterium bovis - Michel, Anita Luise (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2015.